2022
DOI: 10.3390/ani12060681
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Taxonomy Revealed Genetic Differences in Morphologically Similar and Non-Sympatric Scoliodon macrorhynchos and S. laticaudus

Abstract: Previous examination of the mitochondrial NADH2 gene and morphological characteristics led to the resurrection of Scoliodon macrorhynchos as a second valid species in the genus, in addition to S. laticaudus. This study applied an integrated taxonomic approach to revisit the classification of the genus Scoliodon based on new materials from the Malaysian Peninsula, Malaysian Borneo and Eastern Bay of Bengal. Mitochondrial DNA data suggested the possibility of three species of Scoliodon in the Indo-West Pacific, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 63 publications
(65 reference statements)
0
9
0
Order By: Relevance
“…The combined records from various studies had excluded species that were unaccepted in World Register of Marine Species (WORMS) ( Cephaloscyllium circulopullum and Narcine indica ) and species that had been verified as absent from Malaysian waters ( Brevitrygon walga and B. imbricata in Last et al [ 13 ]). These records have been improved in terms of classification within the family Dasyatidae [ 13 ]; incorporation of the revision of Telatrygon species in Malaysian waters [ 14 ]; delimitation of cryptic species in Neotrygon kuhlii complexes [ 15 , 74 , 76 ]; new recorded species in Malaysian water, including Carcharhinus tjutjot [ 10 ], Fluvitrygon kittipongi, and F. oxyrhyncha [ 16 , 17 ]); and Scoliodon laticaudus [ 35 ] (previously revised as S. macrorhynchos in Last et al [ 6 ]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combined records from various studies had excluded species that were unaccepted in World Register of Marine Species (WORMS) ( Cephaloscyllium circulopullum and Narcine indica ) and species that had been verified as absent from Malaysian waters ( Brevitrygon walga and B. imbricata in Last et al [ 13 ]). These records have been improved in terms of classification within the family Dasyatidae [ 13 ]; incorporation of the revision of Telatrygon species in Malaysian waters [ 14 ]; delimitation of cryptic species in Neotrygon kuhlii complexes [ 15 , 74 , 76 ]; new recorded species in Malaysian water, including Carcharhinus tjutjot [ 10 ], Fluvitrygon kittipongi, and F. oxyrhyncha [ 16 , 17 ]); and Scoliodon laticaudus [ 35 ] (previously revised as S. macrorhynchos in Last et al [ 6 ]).…”
Section: Discussionmentioning
confidence: 99%
“…The field identification of several closely related sharks (including carcharhinid, sphyrnid, and triakid sharks) and batoids (Myliobatiformes and skates) is often challenging, which might result in inaccurate species compositions and diversity in catch reports [ 32 , 33 ]. Moreover, only a few detailed studies have been conducted on the taxonomy and diversity of elasmobranchs in Malaysia [ 9 , 34 , 35 ]. The lack of data in this field is mainly due to large specimen sizes, ethical reasons, lack of experienced taxonomists, and high field survey costs, which, in turn, render accurate identification more challenging [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…As far as the present authors are aware, molecular divergence times have not been estimated for the extant Rhizoprionodon species, and few reliable reports of these species can be found in the fossil record. Lim et al (2022) suggested a relatively recent divergence for the closely related extant Scoliodon species, and Lim et al (2010) estimated an early to middle Miocene divergence for the extant sphyrnids. The morphological dental similarities between Rhizoprionodon , Scoliodon , and some of the sphyrnids (especially Eusphyra ) suggest that the extant Rhizoprionodon species also diverged during the Miocene (as was suggested by Herman, Hovestadt-Euler & Hovestadt (1991) ).…”
Section: Discussionmentioning
confidence: 99%
“…However, molecular data alone do not replace traditional taxonomy in the delimitation of species [72]. This integrative approach has been used over the years and has proven to be quite effective in elasmobranchs [72][73][74][75][76] and in other groups of organisms [76,77].…”
Section: Discussionmentioning
confidence: 99%
“…Incorrect identifications or identifications at a higher taxonomic level often reflect high numbers of BINs, which are generally associated with ghost species but may also indicate undescribed species [5,75,[78][79][80]. We also highlight that the barcode DNA in fish often does not reveal the genetic peculiarities existing in the groups, mainly in species with taxonomic complexity such as that already known to exist in Squalus [3,21,25,26], resulting in the need to use other genetic markers [36,[81][82][83], or associations with morphological studies, for an integrated taxonomic approach [73,74,83].…”
Section: Discussionmentioning
confidence: 99%